Evidence for positive selection in putative virulence factors within the Paracoccidioides brasiliensis species complex (2008)
ABSTRACT: Paracoccidioides brasiliensis is a dimorphic fungus that is the causative agent of paracoccidioidomycosis, the most important prevalent systemic mycosis in Latin America. Recently, the existence of three genetically isolated groups in P. brasiliensis was demonstrated, enabling comparative studies of molecular evolution among P. brasiliensis lineages. Thirty-two gene sequences coding for putative virulence factors were analyzed to determine whether they were under positive selection. Our maximum likelihood–based approach yielded evidence for selection in 12 genes that are involved in different cellular processes. An in-depth analysis of four of these genes showed them to be either antigenic or involved in pathogenesis. Here, we present evidence indicating that several replacement mutations in gp43 are under positive balancing selection. The other three genes (fks, cdc42 and p27) show very little variation among the P. brasiliensis lineages and appear to be under positive directional selection. Our results are consistent with the more general observations that selective constraints are variable across the genome, and that even in the genes under positive selection, only a few sites are altered. We present our results within an evolutionary framework that may be applicable for studying adaptation and pathogenesis in P. brasiliensis and other pathogenic fungi. Author Summary The fungus Paracoccidioides brasiliensis is the causative agent of paracoccidioidomycosis, a severe pulmonary mycosis that is endemic to Latin America, where an estimated 10 million people are infected with the fungus. Despite the importance of this disease, we know little about the ecological and evolutionary history of this fungus. Here, we present a survey of genetic variation in putative virulence genes in P. brasiliensis in what constitutes the first systematic approach to understand the molecular evolution of the fungus. We used a population genetics approach to determine the role has natural selection played in the coding genes for proteins involved in pathogenesis. We found that nonsynonymous mutations are more common in genes that code for virulence factors than in housekeeping genes. Our results suggest that positive selection has played an important role in the evolution of virulence factors of P. brasiliensis and is therefore an important factor in the host–pathogen dynamics. Our results also have implications for the possible development of a vaccine against paracoccidioidomycosis, since gp43—the main vaccine candidate—has a high level of polymorphism maintained by natural selection.